KONTEKS TUTURAN BAHASA HUMOR DALAM AKUN YOUTUBE MAJELIS LUCU INDONESIA PADA “KONTEN DEBAT KUSIR” - Deny Sulistyawati; Markhamah Markhamah; Atiqa Sabardila (Universitas Muhammadiyah Surakarta, 2020)
This study was aimed to explore the context of speech found in Majlis Lucu Indonesia You tube account in the content of debat kusir. The data were in the form of utterances collected from six videos entitled “Membantah Argument Deddy Corbuzier,” “Respect Reza Octovian,” “Atta Halilintar Tidak Bersalah,” “Lagi-Lagi Atta Halilintar,” “Cara MenaklukanDeddyCorbuzier,” dan “TausiyahUntuk K-Poppers.” The research approach was descriptive qualitative, particularly the reference and the documentary method. The data collection techniques used were listening, note-taking, and documentary techniques. The result indicated that there were five contexts in this study, namely, describing contextual contexts, existential contexts, situational contexts, practical contexts, and psychological contexts.